Linking the planetary ephemeris to the International Celestial Reference Frame. (5th March 2015) - Folkner, W. M.; Border, J. S.
Abstract: The largest uncertainty in the ephemerides for the inner planets is in the orientation of the dynamical system to the celestial reference frame. A program of VLBI measurements of spacecraft in orbit about Venus and Mars has been performed to reduce the orientation uncertainty to 0.2 milliarcseconds.